The Labour Market Experience of University Graduates in Sri Lanka - Chandrasiri, Sunil (My University, 2008)
Graduate unemployment has been a major socio-politico-economic problem in the small open economy of Sri Lanka for the past 35 years. The nature of the problem, causal factors and policy responses are examined in this paper with a special focus on the role of higher education within a highly competitive and knowledge-based economic environment. The evidence reveals that the problem of graduate unemployment is not entirely a university problem. It is mostly a structural issue that requires a positive response from both demand and supply sides of the labour market. On the demand side, it involves high economic growth promoted through institutional and policy support, while on the supply side, universities need to be more dynamic and market oriented in the delivery of graduate output.